COCCÍDEOS DO BRASIL V. COCCIDAE Ceroplastes (Octoceroplastes) hampeli Lizer, 1919 - Vernalha, Milton M.; Gabardo, J. C.; Silva, R. P. da (Acta Biológica Paranaense, 1974)
<hpml> COCCÍDEOS DO BRASIL V. COCCIDAE Ceroplastes (Octoceroplastes) hampeli Lizer, 1919